LET THE ACID AND BASE FLASH OUT! - Lai, Emilia Yie Lin; Lee, Tien Tien (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research is to design and develop the Acid-Base e-Flashcard (ABeF) and investigate student teachers’ perception towards the usability of ABeF. The research design of this study is design and development research. The ABeF development process was based on five phases in ADDIE model. Three instruments were used in this research, which are the content validity evaluation form, reliability questionnaire and usability questionnaire. Two Chemistry lecturers have been appointed to validate the content validity of ABeF. A total of 32 semester seven student teachers from Bachelor of Education (Chemistry) program were chosen as the respondents to identify the reliability of ABeF and usability questionnaire during the pilot study. A total of 201 student teachers from the same program were involved in the field study. The findings show that the Cohen kappa coefficient value for the validity of ABeF was 1.00. The overall reliability value for ABeF was 0.98. The mean values for the usability of ABeF in terms of usefulness, satisfaction and ease of use were 3.82 (SD = 0.39), 3.84 (SD = 0.37) and 3.84 (SD = 0.37), respectively. In conclusion, ABeF has high validity, reliability and usability index. The implication of this study is ABeF can help the teachers and student teachers to teach acid and base topic in a more interesting way. Besides, form four Chemistry students can learn acid and base topic better with the use of ABeF that can be visualized.